PEMILIHAN MENU DI KANTIN SESUAI MINAT MAHASISWA DENGAN MENGGUNAKAN METODE PROFILE MATCHING - Firliana, Rina; Indriati, Rini; Daniati, Erna; Nugroho, Arie; Niswatin, Ratih Kumalasari; Arie, Theo Yan (Nusantara of Engineering (NOE), 2025)
A canteen business on a campus or college is very profitable for entrepreneurs. Where the canteen serves a variety of food for sale. However, with the many menus provided, it has an effect on cost and labor. Because with the many menus provided, the seller must prepare all the menus, but for the menu, there are those that are sold a lot and some are only sold a few or a little so that the menu that is sold a little is wasted. For this reason, this research aims to help canteen sellers to be more efficient in serving menus that are most in demand by students and which are not in demand by students so that they do not suffer big losses. For this reason, in this study, a decision support system is applied using the Profile Matching method with five criteria used, namely selling price, production price, serving, taste and manufacturing time. For menu options consisting of instant noodles, pecel rice, vegetable rice, kremes chicken, kremes tempeh and soto. From the results of the research, the results of the food menu were obtained which became the main choice among the other alternatives offered. So that canteen sellers can prepare the menu that is most interested in cooking or provided more than the menu that is less in demand and cooked less. And the raw materials prepared are adjusted to the interest rating calculated using the profile matching method.